Selected Topics on Advanced Information Systems Engineering: Editorial Introduction to the Issue 5 of CSIMQ - Grabis, Janis; Sandkuhl, Kurt (Complex Systems Informatics and Modeling Quarterly, 2015)
The 5th issue of the journal on Complex Systems Informatics and Modeling (CSIMQ) presents extended versions of five papers selected from the CAiSE Forum 2015. The forum was part of the 27th edition of international Conference on Advanced Information Systems engineering (CAiSE 2015), which took place in June 2015 in Stockholm, Sweden. Information systems engineering draws its foundation from various interrelated disciplines including, e.g., conceptual modeling, database systems, business process management, requirements engineering, human computer interaction, and enterprise computing to address various practical challenges in development and application of information systems. The guiding subjects of CAiSE 2015 were Creativity, Ability, and Integrity. The CAiSE Forum aimed at presenting and discussing new ideas and tools related to information systems Engineering.